2018
DOI: 10.1002/mnfr.201800448
|View full text |Cite
|
Sign up to set email alerts
|

Essential Fatty Acids Linoleic Acid and α‐Linolenic Acid Sex‐Dependently Regulate Glucose Homeostasis in Obesity

Abstract: Long-term intake of LA (for women) and ALA may have a protective effect on T2D development for obese/overweight subjects through sex-specific gut microbiota modulation and gut-adipose axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
3
17
0
1
Order By: Relevance
“…Previous literature has also revealed a critical role of dietary factors, including dietary fat [5], in shaping gut microbial composition. Increased consumption of saturated fat induces intestinal dysbacteriosis and endotoxemia [6,7], whereas polyunsaturated fatty acids (PUFAs) restore gut micro-ecological equilibrium and relieve inflammation [8][9][10][11]. Notably, emerging evidence shows that marine n-3 PUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are able to ameliorate insulin resistance (IR) in rodents probably via regulating adipocytokines secretion [12][13][14], inhibiting adipose remodeling [15], lowering inflammation [16][17][18], and enhancing mitochondrial function and β-oxidation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has also revealed a critical role of dietary factors, including dietary fat [5], in shaping gut microbial composition. Increased consumption of saturated fat induces intestinal dysbacteriosis and endotoxemia [6,7], whereas polyunsaturated fatty acids (PUFAs) restore gut micro-ecological equilibrium and relieve inflammation [8][9][10][11]. Notably, emerging evidence shows that marine n-3 PUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are able to ameliorate insulin resistance (IR) in rodents probably via regulating adipocytokines secretion [12][13][14], inhibiting adipose remodeling [15], lowering inflammation [16][17][18], and enhancing mitochondrial function and β-oxidation [19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a series of studies reported the effects of n-3 PUFAs or related carriers rich in n-3 PUFAs on the gut microbiota of animals or humans, including healthy volunteers (6), overweight individuals with metabolic syndrome (7), breast cancer survivors (8), mice with alcohol-induced liver injury (9), obese mice (4), early-life antibiotic exposure-induced obese mice (10), rats fed a high-fat diet (11), individuals with nonalcoholic fatty liver disease (12), and early-life-stress rats (13). Most of these studies focus on the effects of EPA and DHA on the gut microbiota of animals and humans with related diseases, and there are few reports on the effect of ALA monomers on the gut microbiota (14)(15)(16).…”
mentioning
confidence: 99%
“…Copper-fructose interaction-induced metabolic effects exhibit sex dimorphism (23,25). Sex speci c alterations of gut microbiota in response to a speci c diets have been demonstrated in a variety of studies (57)(58)(59). Given that the gut microbiota play a causal role in driving the development of metabolic diseases, we aimed to determine whether sex-speci c alterations of the gut microbiota are linked to hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%